Afghanistan's 2014 election : need for strong mandate - Halimullah Kousary (2014)
Afghanistan is on the cusp of its first ever non-violent transition of power in its modern history. On 5 April 2014, the third presidential election since the fall of the Taliban regime in 2001 will be held. What are the prospects for reconciliation with the Taliban?